THE BEOWULF POET'S SENSE OF DECORUM - Neidorf, Leonard (Traditio, 2021)
This paper reassesses the relationship between Beowulf and the legendary tradition that existed prior to its composition. Through wide-ranging comparative analysis, it identifies probable departures from the antecedent tradition and argues that these departures are best understood not in impersonal terms, as Christian reactions to a pagan tradition, but in terms of a singular poet's sense of decorum, which was not possessed by all Christian authors throughout the Middle Ages. Focusing on interpretive controversies related to matters such as slavery, kin-slaying, the posthumous fate of pagans, and violence orchestrated by women, this paper argues that a series of ostensibly unrelated problems in the poem's critical literature could be resolved with a single coherent explanation: namely, that Beowulf was composed by a poet who sought to preserve as much as possible from the antecedent tradition, while not hesitating to obscure indecorous features and to express value judgments alien to the inherited material. The Beowulf poet's sense of decorum is shown herein to be idiosyncratic yet coherent and pervasive, responsible for various minor departures from tradition and for the selection of the untraditional protagonist around which the poem is structured.